Experiences of Political Participation in Learning Environments: Learner-Orientation in Civic Education (Pedagogical Horizons, 2021)
Political education aims to provide orientation in an ambivalent, complex, rapidly changing social reality. Against the background of a social acceleration that also includes schools, the present article pleads for a decelerated political education that is oriented towards the perspectives of the learners. Using the example of data obtained from interviews with students, it is shown how the topic of “political participation” can be treated in a learner-oriented as well as concept-based manner.
Keywords: Political Partizipation; learner-orientation; democracy; school